Bomond . Bomond . Beau Monde . Бомонд - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Interview with the deputy of State Duma Grigorii IAvlinskii. Featured in the program: IAvlinskii, Grigorii Alekseevich (Deputy of the State Duma) Contributors: Ganapol'skii, Matvei (Anchor); Venediktov, Aleksei Alekseevich (Anchor) Интервью с депутатом Государственной Думы Григорием Явлинским. В программе участвуют: Явлинский, Григорий Алексеевич (Депутат Государственной Думы) Создатели: Ганапольский, Матвей (Ведущий/Ведущая); Венедиктов, Алексей Алексеевич (Ведущий/Ведущая)